2019
DOI: 10.3390/ijms20102458
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Protocols to Obtain Insulin-Producing Cells from Rat Adipose Tissue: Signaling Pathways and In Vivo Effect

Abstract: Studies using mesenchymal stromal cells (MSCs) as a source of insulin-secreting cells (IPCs) are a promising path in the pursuit for diabetes therapy. Here, we investigate three short-term differentiation protocols in order to generate IPCs from autologous adipose-derived stromal cells (ADSCs) with an expressive insulin-secreting profile in vitro and in vivo, as well as the signaling pathways involved in the chosen differentiation protocols. We extracted and cultured ADSCs and differentiated them into IPCs, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…MSCs can differentiate into insulin-producing cells (IPCs) both in vitro and in vivo, which underlies their potential for treating DM [ 98 ]. The transplantation of IPCs derived from different types of MSCs in vitro is effective in regulating blood glucose levels in experimental diabetic animals [ 99 , 100 , 101 ]. However, although MSCs migrate to the pancreas, the differentiation into IPCs is minimal, and it is not the explanation for the possible regenerative effects induced by cell therapy.…”
Section: Preclinical and Clinical Approaches To Msc In Diabetes-induced Cardiac Complicationsmentioning
confidence: 99%
“…MSCs can differentiate into insulin-producing cells (IPCs) both in vitro and in vivo, which underlies their potential for treating DM [ 98 ]. The transplantation of IPCs derived from different types of MSCs in vitro is effective in regulating blood glucose levels in experimental diabetic animals [ 99 , 100 , 101 ]. However, although MSCs migrate to the pancreas, the differentiation into IPCs is minimal, and it is not the explanation for the possible regenerative effects induced by cell therapy.…”
Section: Preclinical and Clinical Approaches To Msc In Diabetes-induced Cardiac Complicationsmentioning
confidence: 99%
“…One study reported that use of a low-attachment suspension culture method could generate IPC spheroids in the presence of activin A and exendin-4 28 . Additionally, Wartchow et al compared three different formulations of differentiationrelated factors and found that IPCs generated by Timper's protocol had the best insulin secretion profile and could ameliorate hyperglycemia in streptozotocin (STZ)-induced diabetic rats 29 , indicating that IPCs generated via the activin A/ exendin-4 formulation have the potential to treat diabetes. However, spheroids that generate spontaneously during culture on low-attachment plates have some disadvantages such as variability in spheroid size and a lack of nutrients and oxygen in the spheroid core, resulting in a skewed distribution of proliferating, non-proliferating, and apoptotic cells that can lead to cell death during culture or after transplantation 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the various sources of adult stem cells, adipose tissue is an ideal population of stem cells. Adipose tissue contains an abundance of stem cells, which can be obtained by a procedure that is relatively easy, inexpensive and minimally invasive 5,6 . Several studies were conducted to differentiate MSCs into cells that were similar to pancreatic islets and which, when transplanted, proved to be functional and producing insulin in diabetic rats 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue contains an abundance of stem cells, which can be obtained by a procedure that is relatively easy, inexpensive and minimally invasive 5,6 . Several studies were conducted to differentiate MSCs into cells that were similar to pancreatic islets and which, when transplanted, proved to be functional and producing insulin in diabetic rats 6 . Pancreatic progenitor cells (PPCs) give rise to all cell types in the pancreas during development 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation